2022
DOI: 10.4103/aja2021127
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results of testicular torsion in children

Abstract: A retrospective cohort study was conducted at the Children’s Hospital of Chongqing Medical University from November 2004 to December 2020 to investigate the long-term follow-up results after testicular torsion (TT) in children. Boys with TT were divided into the salvage orchiopexy group and the orchiectomy group, and the baseline characteristics, ultrasonographic indications, intraoperative findings, testicular volumes, and adverse events during follow-up were compared. A total of 145 cases were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Oxidative stress in testis tissue is very detrimental due to highly unsaturated fatty acids [28]. It has been previously demonstrated that ischemia/reperfusion damages in testis tissue resulted in testis atrophy and reduction of testicular weight [29]. Several studies previously reported reduced serum testosterone levels due to testicular torsion/detorsion process [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in testis tissue is very detrimental due to highly unsaturated fatty acids [28]. It has been previously demonstrated that ischemia/reperfusion damages in testis tissue resulted in testis atrophy and reduction of testicular weight [29]. Several studies previously reported reduced serum testosterone levels due to testicular torsion/detorsion process [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de investigaciones sugieren que a largo plazo es posible encontrarse con secuelas por el tratamiento, tanto por la orquiectomía como por la orquidopexia (Aggarwal et al, 2022). Los efectos a corto y largo plazo están estrechamente relacionados con la rapidez con las que se brindó un tratamiento; ya que mientras más tiempo se tardó en identificar la TT y llevar a cabo la intervención quirúrgica, fue más difícil salvar el testículo afectado y se mostraron tasas más lentas de recuperación, así como una mayor tendencia a presentar efectos negativos como atrofias testiculares, disminución de la espermatogénesis, bajas concentraciones de testosterona, menos calidad seminal, entre otros (Aggarwal et al, 2022;Yu et al, 2022;. Uno de los efectos adversos frecuentemente observados fue la degeneración testicular acompañada de una reducción del volumen gonadal; considerando que un ochenta y cinco por ciento de la composición masiva del testículo es constituida por estructuras tubulares seminíferas y el volumen testicular es un reflejo de su estado funcional, de acuerdo con Emeka Chukwubuike et al ( 2022), está relacionado con espermatogénesis reducida y fertilidad reducida en la vida adulta.…”
Section: Discussionunclassified